1996
DOI: 10.1021/ja961371b
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Stable Parallel-Stranded Oligonucleotides Containing 5-Methylisocytosine and Isoguanine

Abstract: The polymorphic nature of double-stranded DNA is well established. 1 A common feature of three major families of A-, B-, and Z-DNA duplexes is the antiparallel orientation of the constituent strands. Parallel-stranded DNA (ps-DNA) is a new family of DNA conformations experimentally confirmed in 1988, in which complementary strands have the same 5′-3′ orientation and form reverse Watson-Crick A-T base pairs. 2 Numerous thermodynamic studies revealed that the parallelstranded duplexes melt with considerably lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 14 publications
2
55
0
1
Order By: Relevance
“…22,23 Competition between charge localization and delocalization is of paramount importance in all the fields of chemistry, from molecular reactivity to material properties, and it is of particular significance also for charge transport in DNA, especially because the possible establishment of delocalized hole domains can significantly affect the hole site energies and in turn the hole transfer rates. [33][34][35][36][37][38][39][40][41] By contrast, ESR spectra of short oligonucleotides containing three consecutive Gs do not show any evidence of charge delocalization, 42 and similar conclusions also emerge from several computational studies. 32 Evidence pointing toward the establishment of delocalized hole sites has also been provided by Saito et al, who have shown that oxidative damage to DNA preferentially occurs at sites consisting of two or three consecutive guanines (G).…”
Section: Introductionsupporting
confidence: 54%
“…22,23 Competition between charge localization and delocalization is of paramount importance in all the fields of chemistry, from molecular reactivity to material properties, and it is of particular significance also for charge transport in DNA, especially because the possible establishment of delocalized hole domains can significantly affect the hole site energies and in turn the hole transfer rates. [33][34][35][36][37][38][39][40][41] By contrast, ESR spectra of short oligonucleotides containing three consecutive Gs do not show any evidence of charge delocalization, 42 and similar conclusions also emerge from several computational studies. 32 Evidence pointing toward the establishment of delocalized hole sites has also been provided by Saito et al, who have shown that oxidative damage to DNA preferentially occurs at sites consisting of two or three consecutive guanines (G).…”
Section: Introductionsupporting
confidence: 54%
“…The IPs (corresponding to the free energy of the hole) obtained by the ab initio Hartree−Fock (HF) molecular orbital (MO) calculations 19,20 are smaller for the longer guanine run. These calculations were performed for the DNA oligomers without a backbone in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…These oligomers, except for the iG/iC-containing oligomers, were commercially synthesized by Amersham Pharmacia biotech Co., Ltd. (Tokyo). Oligomers iC1, iC2, RiG1, and RiG2 were chemically synthesized (Sugiyama et al, 1996). Two successive transitions were performed in a reaction mixture containing oligomer Tran1 (3 mM), 2 mM MgCl 2 , dATP, dGTP, and dCTP (250 mM each), 2 units of AmpliTaq DNA polymerase (Perkin-Elmer), and the PCR buffer provided by the supplier.…”
Section: Methodsmentioning
confidence: 99%